A New Breed Of Home Studio Producer?: Agency And The Idea ‘Tracker’ In Contemporary Home Studio Music Production - Tuomas Auvinen (Association for the Study of the Art of Record Production, 2022)
In this article my aim is to explore the creative and collaborative agency of an aspiring Finnish Helsinki-based pop-music producer Mikke Vepsäläinen. In a detailed ethnographic case study of the home studio production of a song published in April 2016, I discuss the producer’s agency through the idea of being a “tracker” or “tracking”. This terminology is commonly used in contemporary pop music production to describe the agency and role of the producer. Yet it has not yet been addressed in studies or written accounts on music production that I’m aware of.